Time to talk about parents of ill children - Xiang, Yifan; Long, Erping; Liu, Zhenzhen; Lin, Haotian (Annals of Translational Medicine, 2019)
The biopsychosocial medical model was proposed to emphasize the role of mentality and environment as significant as biological factors in disease recovery (1). Based upon the consensus of psychological factors in the biopsychosocial medical model, psychological intervention related programmes have been implemented to ensure mental health and improve the prognosis of physiologically ill patients (2). Nevertheless, there have been few social factors related projects since the environments of patients seem hard to change. However, parents of ill children play a pivotal role in children’s social environment, providing an entry point to make a difference in ill children’s recovery.